Joint detection/decoding algorithms for non-binary low-density parity-check codes over inter-symbol interference channels - Zhao, Shancheng; Lu, Zhifei; Ma, Xiao; Bai, Baoming (IET communications, 2013)
This study is concerned with the application of non-binary low-density parity-check (NB-LDPC) codes to binary input inter-symbol interference channels. Two low-complexity joint detection/decoding algorithms are proposed. One is referred to as max-log-MAP/X-EMS algorithm, which is implemented by exchanging soft messages between the max-log-MAP detector and the extended min-sum (EMS) decoder. The max-log-MAP/X-EMS algorithm is applicable to general NB-LDPC codes. The other one, referred to as Viterbi/GMLGD algorithm, is designed in particular for majority-logic decodable NB-LDPC codes. The Viterbi/GMLGD algorithm works in an iterative manner by exchanging hard-decisions between the Viterbi detector and the generalised majority-logic decoder (GMLGD). As a by-product, a variant of the original EMS algorithm is proposed, which is referred to as µ-EMS algorithm. In the µ-EMS algorithm, the messages are truncated according to an adaptive threshold, resulting in a more efficient algorithm. Simulations results show that the max-log-MAP/X-EMS algorithm performs as well as the traditional iterative detection/decoding algorithm based on the BCJR algorithm and theQ-ary sum–product algorithm, but with lower complexity. The complexity can be further reduced for majority-logic decodable NB-LDPC codes by executing the Viterbi/GMLGD algorithm with a performance degradation within one dB. These algorithms provide good candidates for trade-offs between performance and complexity.